Evaluation of Amblyopia in School Going Children - Pawan N. Jarwal; Rekha Singh (Delhi Journal of Ophthalmology)
Background and Objective: Amblyopia is the most common cause of monocular vision loss in children and as amblyopia is a major preventable and treatable cause of pediatric low vision, early detection and treatment of amblyopia is very important to reduce the prevalence of amblyopia. This study was done to determine the prevalence of amblyopia in school going children in the age group of 5-15 years in and around Jaipur and also to detect the types of amblyopia in these children. Materials and Methods: Cross sectional and time bound study, in which 4020 school children in the age group of 5-15 years underwent screening. Amblyopia was diagnosed in eyes with reduced best corrected visual acuity in the absence of any other cause. Results: Amblyopia was diagnosed in 44 children. Prevalence of amblyopia in our study was found to be 1.1 %. The underlying amblyogenic causes assessed were anisometropia (29.5%), strabismus (25%), combined mechanism amblyopia (15.9%), meridional amblyopia (13.6%), ametropic amblyopia (11.6%), and the least was that of visual deprivation amblyopia being 4.5%. No statistically significant associations were found in the geographical distribution, or in the gender distribution. The most frequent pattern of strabismus was exotropia. A higher percentage of moderate degree of amblyopia (64%) and more of unilateral cases of amblyopia (26) were detected. There were an equal number of hypermetropes and myopes, majority were given spectacle correction. All 44 amblyopes were prescribed occlusion therapy. Conclusion: Prevalence of amblyopia was found to be 1.1% in our study. The results indicate the importance of screening school going children for amblyopia and the importance of early detection and treatment.